2009
DOI: 10.1007/s00436-009-1467-0
|View full text |Cite
|
Sign up to set email alerts
|

Theileria-infected cell line from an African buffalo (Syncerus caffer)

Abstract: Mononuclear cells were isolated from the peripheral blood of a buffalo infected with a Theileria sp. using density gradient centrifugation, and the cells were put into culture flasks covered by a monolayer of bovine endothelial cells. Twenty days after culture initiation, cells containing macroschizonts were detected in Giemsa-stained smears. The first subculture was carried out on day 45 of culture propagation. Subsequently, infected cells were subcultured twice a week, and each time 1 to 2 x 10(6) per millil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…The establishment of a T. sp. (buffalo) cell line from a buffalo of South African origin showed that on 18S level it is identical to the parasite described from East Africa (Zweygarth et al 2009). T. sp.…”
Section: Discussionmentioning
confidence: 59%
“…The establishment of a T. sp. (buffalo) cell line from a buffalo of South African origin showed that on 18S level it is identical to the parasite described from East Africa (Zweygarth et al 2009). T. sp.…”
Section: Discussionmentioning
confidence: 59%
“…(bougasvlei). Morphologically no distinguishing features are known (Zweygarth et al 2009). Theileria sp.…”
Section: Discussionmentioning
confidence: 99%
“…For all assays the gold standard T. parva positive (KNP102) (Sibeko et al 2008), T. sp. (buffalo) positive (Buffalo 114) (Zweygarth et al 2009) and negative (9426) controls used for routine diagnostics were included. The negative control was born and raised in a herd under quarantined tick-free conditions.…”
Section: Buffalo Samples and Dna Extractionmentioning
confidence: 99%
“…Theileria buffeli and the hitherto uncharacterized Theileria sp. (buffalo) have also been identified in some buffalo populations in South Africa (Stoltsz, 1996;Zweygarth et al, 2009;Mans et al, 2011) and the local tick vectors of these parasites are unknown. Theileria sp.…”
Section: Introductionmentioning
confidence: 99%